ANALISIS EFISIENSI EFEKTIVITAS PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH DALAM RANGKA OPTIMALISASI PENERIMAAN PENDAPATAN ASLI DAERAH KABUPATEN HULU SUNGAI SELATAN - Ainaya Al Fatihah; Muhammad Saleh (PPJP Universitas Lambung Mangkurat, 2020)
The purpose of this study is to determine the rate of efficiency and effectiveness of regional tax revenue in the Hulu Sungai Selatan Regency and to determine the rate of growth and its contribution to regional taxes and regional own-source revenue (PAD) of the Hulu Sungai Selatan Regency. Local tax as one component of local revenue contained in the original regional income imposed on the residents of the area by the regional government without obtaining direct contra from the tax paid.The method used in this research is a quantitative descriptive study with the analysis method of efficiency, effectiveness, contribution and growth rate using secondary data in the form of the realization of the regional income and expenditure budget obtained from the Regional Finance Agency of the South Hulu Sungai Regency.Keyword: Efficiency and effectiviness, local tax, local revenue